Baseline Corrected QT Interval Dispersion Is Useful to Predict Effectiveness of Metoprolol on Pediatric Postural Tachycardia Syndrome - Wang, Yuanyuan; Sun, Yan; Zhang, Qingyou; Zhang, Chunyu; Liu, Ping; Wang, Yuli; Tang, Chaoshu; Jin, Hongfang; Du, Junbao (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The study was designed to explore the role of baseline-corrected QT interval dispersion (QTcd) in predicting the effectiveness of metoprolol on pediatric postural tachycardia syndrome (POTS). Methods: There were two groups in the study, the discovery group and the validation group. The children with POTS in the discovery group were treated with oral metoprolol, with the completed necessary medical records, head-up tilt test, blood chemistry, and 12-lead electrocardiogram (ECG) before treatment at the pediatrics of Peking University First Hospital, China. According to whether the symptom score (SS) was reduced by more than 2 points after administration with oral metoprolol as compared with that before treatment, the children with POTS were separated into responders and non-responders. The demographic characteristics, hemodynamic indicators, and the QTcd of the two groups were compared, and the estimate of the baseline QTcd in predicting the treatment response to metoprolol was tested through ROC analysis. Another 24 children suffering from POTS, with the completed necessary medical records, and administrated with metoprolol at the pediatrics of Peking University First Hospital were included in the validation group. The sensitivity, specificity, and accuracy of the baseline QTcd in the prediction of the effectiveness of metoprolol on POTS were validated in children. Results: The pre-treatment baseline QTcd in responders treated with metoprolol was longer than that of the non-responders in the discovery group [(66.3 ± 20.3) ms vs. (45.7 ± 19.9) ms, P = 0.001]. The baseline QTcd was negatively correlated with SS after metoprolol treatment (r = -0.406, P = 0.003). The cut-off value of baseline QTcd for the prediction of the effectiveness of metoprolol on pediatric POTS was 47.9 ms, yielding a sensitivity of 78.9% and a specificity of 83.3%, respectively. The validation group showed that the sensitivity, specificity and accuracy of the baseline QTcd ≥ 47.9 ms before treatment for estimating the effectiveness of metoprolol on POTS in children were 73.7%, 80.0%, and 75.0%, respectively. Conclusion: Corrected baseline QTcd is effective for predicting the effectiveness of metoprolol on pediatric POTS.